Selected cognitive factors and speech recognition performance among young and elderly listeners. - Gordon-Salant S; Fitzgibbons PJ (Journal of Speech, Language & Hearing Research, 1997)
The influence of selected cognitive factors on age-related changes in speech recognition was examined by measuring the effects of recall task, speech rate, and availability of contextual cues on recognition performance by young and elderly listeners. Stimuli were low and high context sentences from the R-SPIN test presented at normal and slowed speech rates in noise. Response modes were final word recall and sentence recall. The effects of hearing loss and age were examined by comparing performances of young and elderly listeners with normal hearing and young and elderly listeners with hearing loss. Listeners with hearing loss performed more poorly than listeners with normal hearing in nearly every condition. In addition, elderly listeners exhibited poorer performance than younger listeners on the sentence recall task, but not on the word recall task, indicating that added memory demands have a detrimental effect on elderly listeners' performance. Slowing of speech rate did not have a differential effect on performance of young and elderly listeners. All listeners performed well when stimulus contextual cues were available. Taken together, these results support the notion that the performance of elderly listeners with hearing loss is influenced by a combination of auditory processing factors, memory demands, and speech contextual information.